STRATEGI PEMIMPIN POPULIS BARU INDONESIA MENCAPAI KEKUASAAN - Imelda Masni Juniaty Sianipar (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2015)
AbstractIndonesia has already had a populist leader, Ir.Soekarno. He is the first President of the RepublicIndonesia. Sukarno is categorized as a populistleader because He is charismatic and close to thepeople. In 2014, Indonesia has witnessed thepresence of populist leader in national politicalarena. The new populist leader is Joko Widodo orwho is wellknown as Jokowi. This figure was chosenby the majority of the people of Indonesia as apresident because it was believed that Jokowi has apopulist style leadership. He is also close to thepeople. This paper will specifically explain Jokowi’sstrategies as a new populist leader in order to gainpower. This paper argues that in order to gainpower and also to get the support from Indonesianpeople, Jokowi relies on his organizationalexperiences, skills, leadership and achievements.He also built a coalition with organized societyespecially with PDI-P participant and alsounorganized society who is known as RelawanJokowi. The last strategy of Jokowi is to promotedemand policy oriented. Based on those strategies,this paper categorizes Jokowi as a rational populistleader.Keywords: populist leader, Jokowi, power,Indonesia, rational populism. AbstrakIndonesia pernah memiliki pemimpin populis yaituIr. Soekarno, Presiden Pertama Republik Indonesia.Soekarno dikategorikan sebagai pemimpin populiskarena memiliki gaya kepemimpinan yangkharismatik dan dekat dengan rakyat. Pada tahun2014, Indonesia kembali menyaksikan hadirnyapemimpin populis di kancah perpolitikan nasional.Pemimpin populis baru tersebut adalah JokoWidodo atau akrab dikenal dengan Jokowi. Tokohini dipilih oleh mayoritas rakyat Indonesia sebagaipresiden karena diyakini memiliki karakterkepemimpinan populis dan dekat dengan rakyat.Tulisan ini secara khusus akan membahas strategiJokowi sebagai pemimpin populis Indonesia barudalam rangka mencapai kekuasan. Tulisan iniberargumen bahwa Jokowi mengandalkanpengalaman organisasi, skill dan leadership danprestasi yang dimilikinya, membangun koalisi baikdengan masyarakat terorganisir maupun yangtidak terorganisir serta mengedepankan kebijakanyang berorientasi pada demand (tuntutan) dalamrangka mendapatkan dukungan rakyat untukmencapai kekuasaan. Karenanya, Tulisan inimengkategorikan Jokowi sebagai pemimpinpopulis rasional.Kata kunci: pemimpin populis, Jokowi, kekuasaan,Indonesia, populisme rasional